2009
DOI: 10.21608/asejaiqjsae.2009.3244
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Common Bean (Phaseolus Vulgaris L.) in Response to Rhizobium Inoculation, Nitrogen and Molybdenum Fertilization

Abstract: Two field trials were carried out in two successive growing seasons of 2006 and 2007 at Elbehara Governerate-Faculty of Agriculture to study the combination effects of seed inoculation (with Rhizobium and without), nitrogen fertilization with (0, 48, 96 kg N/ha) and foliar molybdenum application(0 and 30 g Mo/l as sodium molybdate) on plant height, branch number, plant fresh weight, plant dry weight, average number of green pods per plant and green pods yield ha-1 as well as nitrogen and molybdenum contents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…The restricted N availability for common beans cultivated organically without GM (SM + BR) is indicated by reduced total N concentrations in pods produced. Similar yield responses of common beans to sub-optimal soil N availability have also been reported by Chekanai et al [ 35 ], Elkhabit [ 36 ], Karasu et al [ 37 ], and Silva et al [ 38 ], who cultivated crops for either green pods, or dry seeds. The beneficial effect of GM application for organically grown common yield seen here, is in accordance with the study of Gatsios et al [ 12 ], who also found that the incorporation of animal manure and GM, including faba beans, enhanced the yield of a subsequent tomato crop.…”
Section: Discussionsupporting
confidence: 81%
“…The restricted N availability for common beans cultivated organically without GM (SM + BR) is indicated by reduced total N concentrations in pods produced. Similar yield responses of common beans to sub-optimal soil N availability have also been reported by Chekanai et al [ 35 ], Elkhabit [ 36 ], Karasu et al [ 37 ], and Silva et al [ 38 ], who cultivated crops for either green pods, or dry seeds. The beneficial effect of GM application for organically grown common yield seen here, is in accordance with the study of Gatsios et al [ 12 ], who also found that the incorporation of animal manure and GM, including faba beans, enhanced the yield of a subsequent tomato crop.…”
Section: Discussionsupporting
confidence: 81%